Permanently densified SiO2 glasses: a structural approach. (27th July 2015) - Martinet, C; Kassir-Bodon, A; Deschamps, T; Cornet, A; Le Floch, S; Martinez, V; Champagnon, B
Abstract: Densified silica can be obtained by different pressure and temperature paths and for different stress conditions, hydrostatic or including shear. The density is usually the macroscopic parameter used to characterize the different compressed silica samples. The aim of our present study is to compare structural modifications for silica glass, densified from several routes. For this, densified silica glasses are prepared from cold and high temperature (up to 1020 °C) compressions. The different densified glasses obtained in our study are characterized by micro-Raman spectroscopy. Intertetrahedral angles from the main band relative to the bending mode decrease and their values are larger for densified samples from high temperature compression than those samples from cold compression. The relative amount of 3-membered rings deduced from the D2 line area increases as a function of density for cold compression. The temperature increase during the compression process induces a decrease of the 3 fold ring population. Moreover, 3 fold rings are more deformed and stressed for densified samples at room temperature at the expense of those densified at high temperature. Temperature plays a main role in the reorganization structure during the densification and leads to obtaining a more relaxed structure with lower stresses than glasses densified from cold compression. The role of hydrostatic or non-hydrostatic applied stresses on the glass structure is discussed. From the Sen and Thorpe central force model, intertetrahedral angle average value and their distribution are estimated.